Blockade of the Adenosine 2A Receptor Mitigates the Cardiomyopathy Induced by Loss of Plakophilin-2 Expression - Cerrone, Marina; van Opbergen, Chantal J. M.; Malkani, Kabir; Irrera, Natasha; Zhang, Mingliang; Van Veen, Toon A. B.; Cronstein, Bruce; Delmar, Mario (Frontiers in Physiology, 2018)
Abstract Background: Mutations in plakophilin-2 (PKP2) are the most common cause of familial Arrhythmogenic Right Ventricular Cardiomyopathy, a disease characterized by ventricular arrhythmias, sudden death and progressive fibrofatty cardiomyopathy. The relation between loss of PKP2 expression and structural cardiomyopathy remains under study, though paracrine activation of pro-fibrotic intracellular signaling cascades is a likely event. Previous studies have indicated that ATP release into the intracellular space, and activation of adenosine receptors, can regulate fibrosis in various tissues. However, the role of this mechanism in the heart, and in the specific case of a PKP2-initiated cardiomyopathy, remains unexplored. Objectives: To investigate the role of ATP/adenosine in the progression of a PKP2-associated cardiomyopathy. Methods: HL1 cells were used to study PKP2- and Connexin43 (Cx43)-dependent ATP release. A cardiac-specific, tamoxifen-activated PKP2 knock-out murine model (PKP2-cKO) was used to define the effect of adenosine receptor blockade on the progression of a PKP2-dependent cardiomyopathy. Results: HL1 cells silenced for PKP2 showed increased ATP release compared to control. Knockout of Cx43 in the same cells blunted the effect. PKP2cKO transcriptomic data revealed overexpression of genes involved in adenosine-receptor cascades. Istradefylline (an adenosine 2A receptor blocker) tempered the progression of fibrosis and mechanical failure observed in PKP2cKO mice. In contrast, PSB115, a blocker of the 2B adenosine receptor, showed opposite effects. Conclusion: Paracrine adenosine 2A receptor activation contributes to the progression of fibrosis and impaired cardiac function in animals deficient in PKP2. Given the limitations of the animal model, translation to the case of patients with PKP2 deficiency needs to be done with caution.